Exploring AI prompting and peer feedback in EFL paragraph writing - Moh Hafidz; Mohammad Arief Wahyudi; Mohammad Kurdi Wijaya; Chairuddin; Arfiyan Ridwan (Indonesian Journal of Educational Development (IJED), 2026)
This study investigated the integration of Artificial Intelligence (AI) prompting with peer feedback in the development of paragraph-writing skills in an English as a Foreign Language (EFL) context. Carried out over a semester at a private university in Indonesia, the research involved 37 undergraduate learners. In most cases, learners responded to feedback without AI help and used AI without intervention. Interestingly, nine participants completed all the necessary tasks involving integrating AI with peer feedback in an EFL writing paragraph. Learners used AI to compare their own feedback and subsequently engaged in peer discussion before finalising the draft. Using a descriptive qualitative approach with thematic analysis, data were gathered through observations and questionnaires. The findings indicate that learners developed self-confidence in expressing their ideas through writing and became more self-reliant after completing paragraphs. The process also fostered natural collaboration, although communication among learners remained limited. Learners were able to construct meaningful sentences using simple vocabulary. Additionally, the integration of AI-generated results, enhanced by personalised feedback, supported learning, fostered harmony among learners, and developed reflective skills.